Integrating edTPA into Physical Education Teacher Education: Teacher Educators’ Perceptions and Experiences in Preparing Teacher Candidates - Olsen, Edward B.; Wyant, James D.; Tsuda, Emi; Laughlin, Michael K.; Baxter, Deborah S. (Journal of Teaching in Physical Education, 2024)
Purpose: In the United States, 15 states maintain policies and 25 states represent some level of edTPA affiliation. This study investigated how the edTPA was integrated and aligned into different physical education teacher education (PETE) programs in New Jersey. It also sought to understand teacher educators’ perceptions and experiences in preparing teacher candidates for the edTPA. Methods: This study utilized three data sources: semistructured interviews (n = 4), one focus group interview (n = 1), and documents (n = 17). Data analysis reflected a conventional approach toward qualitative content analysis. Results: In analyzing the data, four themes were established: (a) benefits and drawbacks of edTPA in PETE, (b) goals and success of edTPA in PETE, (c) integrating edTPA into PETE—macro- and microperspectives, and (d) analytic insights into edTPA and future recommendations. Discussion/Conclusion: In states requiring the edTPA, early exposure, scaffolding, curriculum mapping, and a shared mission and vision are critical. In states not requiring the edTPA, programs may want to consider indicators of performance, such as artifacts, reports, elements of the edTPA, university-based assessments, or a portfolio. Regardless of the type of assessment, “a” performance-based assessment may help to determine teacher candidates’ ability to plan, instruct, assess, and reflect.
Keywords: dept.hms; faculty; peer-reviewed; performance-based assessments; preservice teachers

50 years later: Who is teaching adapted physical education? - Laughlin, Michael (Journal of Physical Education, Recreation & Dance, 2024)
The Individuals with Disabilities Education Improvement Act of 2004 ensured millions of American students had a legal right to free and appropriate physical education. Yet, there is confusion about who delivers appropriate adapted physical education (APE). This article reflects on the half century of legally defined APE and a country’s response to preparing teachers for the disability-related demands of the job. A critical perspective is offered with the hope of improving physical educational outcomes for students with disabilities.
_eprint: https://doi.org/10.1080/07303084.2024.2383526
Keywords: dept.hms; peer-reviewed

Associations between weight perception and weight status with perceptions of the body positivity movement - Rupp, K.; McCoy, S.M. (American Journal of Health Promotion, 2024)
Purpose: To explore the relationships between weight status, weight perceptions, and perceptions of the body positivity movement on social media. Design: Cross-sectional. Setting: Online through the Qualtrics platform. Subjects: Participants (N = 521; mean 26.6 ± 5.1 years) were recruited using Qualtrics online panels. Measures: The study survey included questions about participant demographics, weight status, and weight perception. Subjects rated 6 study-specific viewpoint questions about the body positivity movement on a 5pt Likert scale. Analysis: Multinomial logistic regression models adjusted for relevant confounders assessed the associations between objective weight status, perceived weight status, and perceptions of the body positivity movement. Results: Objective weight status was not associated with perceptions of the body positivity movement. Perceptions of weight status were associated with perceptions of the body positivity movement in young women, with those that perceived themselves as overweight more likely (OR = 1.67, P < 0.05) to disagree with the statement that “the body positivity makes people less likely to lose weight.”. However, young women that perceived themselves as having a lower weight status were less likely (OR = 0.54, P < 0.05) to agree with the statement that “the body positivity movement empowered women” as well as “being inclusive of people of all sizes” (OR = 0.56, P < 0.05). Conclusion: Weight perception, rather than objective weight status, may be a stronger predictor of weight bias and views of the body positivity movement. © The Author(s) 2024.
Keywords: body image; body positivity movement; dept.hms; obesity; peer-reviewed; weight perception

Association between exercise program participation and hospitalization of older adults - Wright, D.S.; Zhou, B.; Wright, C.X.; Axtell, R.S.; Mangi, A.; Safdar, B. (American Journal of Preventive Medicine, 2024)
Introduction: Government and insurance sponsored exercise programs have demonstrated decreased hospitalizations, but it is unclear if this is the case for self-referred programs. Methods: In this retrospective cohort study from 2013 to 2020, older adults who participated for at least three months at a community-based exercise center (participants) were compared with those who did not (nonparticipants). Each completed a baseline physical assessment and periodic reassessments thereafter. These data were paired with regional hospital data and a national mortality database. Statistical analysis and modeling were performed from 2020 to 2023. Survival to all-cause hospitalization was assessed with a priori subgroup comparison by gender and cox proportional hazard modeling by age, gender, and comorbidities. Results: The cohort included 718 adults, mean age 69.5 years (SD 8.4), with 411 (57.2%) participants and 307 nonparticipants. Mean follow-up was 26.7 months. Participants had similar baseline measures of fitness (p>0.05) but were more likely to be retired and less likely to have diabetes or prior stroke than nonparticipants. Sustained participation was associated with a reduced rate of all-cause hospitalization (9.0% vs. 12.7%, p=0.02), even when adjusted (HR 0.54; 95% CI 0.34, 0.87, p=0.01). This decrease was noted only in women (p=0.03) but not in men (p=0.49), gender was nonsignificant after adjustment for comorbidities (p=0.15). Conclusions: Exercise program participation was independently associated with decreased risk of all-cause hospitalization, with possible differential effects by gender. Further randomized trials of the benefits of personalized exercise programs are warranted to assess sex- and gender-specific effects. © 2024 Elsevier Inc.
Keywords: dept.hms; peer-reviewed

Physical activity and bullying in adolescents with overweight and obesity - McCoy, S.M.; Rupp, K. (International Journal of Bullying Prevention, 2024)
Background: The relationship between physical activity (PA) and bullying behaviors is unclear among adolescents with overweight/obesity (OW/OB). The current study examined the likelihood of engaging in bullying behaviors by differing physical activity behaviors in adolescents with OW/OB. Method: Analyses included 9114 adolescents with OW/OB, ages 10–17 years, from the combined 2018–2019 National Survey of Children’s Health. Adolescents were grouped by PA level (0 days, 1–3 days, 4–6 days, every day); outcome variables included bullying behaviors (perpetrator, victim, both, or neither), sport participation, behavioral conduct problems, depression, difficulty making new friends, and excessive arguing. Separate adjusted logistic regression models assessed the odds of each outcome comparing differing PA levels. Results: Compared to their inactive peers, adolescents with OW/OB that engaged in at least 1 day of PA were significantly less likely to be victims of bullying (OR = 0.80; 95% CI (0.68, 0.93)) and to be both a bully perpetrator and victim (OR = 0.77; 95% CI (0.64, 0.94)). Participation in sports significantly increased the likelihood of being a bully perpetrator (OR = 1.50; 95% CI (1.06, 2.11)) and decreased the likelihood of being a bully victim (OR = 0.83; 95% CI (0.75, 0.92)) in adolescents with OW/OB. Additionally, adolescents with OW/OB that participated in PA were less likely to experience adverse psychosocial outcomes. Conclusions: Findings suggest PA participation (≥ 1 day/week) may reduce the likelihood of bully victimization and both (perpetration and victimization) and attenuate adverse psychosocial outcomes in adolescents with OW/OB. However, sport participation may increase bully perpetration while decreasing bully victimization in adolescents with overweight/obesity. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.
Keywords: Adolescence; Bullying; Obesity; Physical activity; dept.hms; peer-reviewed

New standards require new approaches to assessment: Is technology the missing piece? - Knipe, R. (Journal of Physical Education, Recreation and Dance, 2024)
How physical education teachers approach standards-based assessment of the new National Physical Education Standards is yet to be determined. But the use of technology for assessments may be one way to support and empower students in the education process toward physical literacy. This article focuses on the ways in which educators have adopted a particular technology, called Plickers, and how its use as an assessment tool can move physical education teachers’ practice forward. © 2024 SHAPE America.
Keywords: dept.hms; peer-reviewed

Leveraging technology to improve access to medical education in anatomy and physiology in resource-limited settings: A mixed methods study - Mora Carpio, A.L.; Romero-Reveron, R.; Vasquez, M.; Bonilla Castillo, J.A.; Gaitán Concepción, L.; Pano Carrera, R.; Liévanos Díaz, D.; Menéndez Conde, B.G.; Montbrun, M.; Espinoza-Luna, A.; Kreiger, J.; Davis, J.L.; et al. (Anatomical Sciences Education, 2024)
This study assesses the acceptability, appropriateness, feasibility, and efficacy of a novel asynchronous video-based intervention for teaching respiratory physiology and anatomy to medical students in resource-limited settings. A series of short video lectures on pleural anatomy, pulmonary physiology, and pathophysiology was created using Lightboard and screen capture technology. These were uploaded to YouTube and Google Drive and made available to 1st-3rd year medical students at two Latin American universities for 1 week. Employing a parallel-convergent mixed methods design, we conducted surveys, focus groups, interviews, and pre/post testing for qualitative and quantitative data. Thematic Analysis was used to analyze qualitative data and McNemar's test for quantitative analysis. Seventy-six students participated. The videos' short format, interactivity, and Lightboard style were highly valued for their flexibility, time efficiency, and educational impact. Students recognized their clinical relevance and trusted their content, suggesting potential applicability in similar settings. Despite infrastructure and connectivity challenges, the use of flexible streaming and downloadable options facilitated learning. Survey results indicated high levels of feasibility (99%), appropriateness (95%), and acceptability (95%), with significant knowledge gains observed (37% correct pre-test answers vs. 56% post-test, p < 0.0001). Our findings demonstrate high acceptability, appropriateness, feasibility, and efficacy of a targeted asynchronous education centered on short-format videos in resource-limited settings, enabling robust learning despite local barriers. Flexible access is key for overcoming localized barriers. Taking an adaptive, learner-centered approach to content creation and delivery to address constraints was pivotal to success. Our modular videos could serve as versatile models for flexible education in resource-constrained settings. © 2024 American Association for Anatomy.
Keywords: Mexico; Venezuela; asynchronous education; dept.hms; distance learning; medical education; peer-reviewed; resource-limited settings; video-based learning

Fostering cultural competence: Exploring client perception in a health coaching intervention among college students - Oh, Seungbin; Benes, Sarah; Yan, Zi (Nursing & Health Sciences, 2024)
Health coaching could be an innovative approach to develop student coaches' cultural competence (CC) among future health professionals. The current mix-method study design explored the impact of an 8-week peer health coaching intervention among college students on CC, from both student health coaches (i.e., students majored in health sciences who completed health coaching training and acted as health coach) and student clients' perspective. Nine student coaches and 24 student clients participated in the study. The quantitative analysis showed an increase in the clients' perceived level of coaches' CC between the pre- and posttest. The qualitative analysis revealed three themes, including varying levels of awareness, respectful and culturally responsive coaching, and cultural connection. Implications and recommendations for educators and researchers are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/nhs.13077
Keywords: cultural competence; cultural humility; dept.hms; health coaching; mixed-method design; peer-reviewed

Spinal cord injury management policies in high school sports as reported by athletic administrators - Scarneo-Miller, Samantha E.; Swartz, Erik E.; Register-Mihalik, Johna K.; Coleman, Kelly A.; Emrich, Christina M.; DiStefano, Lindsay J. (Translational Journal of the American College of Sports Medicine, 2024)
Introduction/Purpose Athletic administrators (AA) in U.S. high schools are uniquely positioned to provide guidance and endorsement for the prevention and management of common sport-related catastrophic injuries, such as the development of a spinal cord injury management (SCIM) policy. The purpose of this project was to evaluate AA’s knowledge of comprehensive SCIM policies in U.S. high schools. Secondarily, we aimed to investigate the factors, facilitators, and barriers to the development and adoption of comprehensive policies. Methods An online questionnaire was distributed to 6423 AA working in U.S.-based high school athletics, with 366 included in the final data analysis. The questionnaire evaluated AA’s knowledge of comprehensive SCIM policies addressing components of adoption, documentation, and communication. The questionnaire was developed based on the 2002 “National Athletic Trainers’ Association Position Statement: Acute Management of the Cervical Spine-Injured Athlete.” The questionnaire also inquired about facilitators and barriers to developing and adopting comprehensive policies. Proportions were calculated for policy adoption, and independent-samples t-tests evaluated the influence of athletic training services on comprehensive SCIM policies. Results About half of AA (49.2%, n = 180/366) reported having all recommended components of a written SCIM policy. AA who had access to an athletic trainer (yes = 62.9%, no = 18.1%, unknown = 19%) were more likely to have a comprehensive SCIM policy compared with those without access (80.6% vs 19.4%, χ21 = 7.091, P = 0.008, prevalence ratio = 1.24, 95% confidence interval = 1.03–1.50). The most commonly reported facilitator (49.9%) was “having a medical professional at the school,” and the main barrier (30.2%) was “my school would need more information, resources, assistance, etc.” Conclusions The findings identify areas for improvement in supporting the health and safety of children in high school participating in interscholastic athletics. Future dissemination and implementation research should develop strategies tailored to individual school community and need to improve SCIM policy adoption and implementation.
Keywords: dept.hms